Antioxidant, Anti-Inflammatory, and Antibacterial Properties of an Achillea millefolium L. Extract and Its Fractions Obtained by Supercritical Anti-Solvent Fractionation against Helicobacter pylori - Marisol Villalva; Jose Manuel Silvan; Teresa Alarcón-Cavero; David Villanueva-Bermejo; Laura Jaime; Susana Santoyo; Adolfo J. Martinez-Rodriguez (MDPI AG, 2022)
The main objective of this work is to evaluate the potential utility of an Achillea millefolium extract (yarrow extract, YE) in the control of H. pylori infection. The supercritical anti-solvent fractionation (SAF) process of YE allowed the obtaining of two different fractions: yarrow's precipitated fraction (YPF), enriched in most polar phenolic compounds (luteolin-7-O-glucoside, luteolin, and 3,5-dicaffeoylquinic acid), and yarrow's separator fraction (YSF), enriched in monoterpenes and sesquiterpenes, mainly containing camphor, artemisia ketone, and borneol. YE was effective in reducing reactive oxygen species (ROS) production in human gastric AGS cells by 16% to 29%, depending on the H. pylori strain. YPF had the highest inhibitory activity (38-40%) for ROS production. YE modulated the inflammatory response in AGS gastric cells, decreasing IL-8 production by 53% to 64%. This IL-8 inhibition also showed a strain-dependent character. YPF and YSF exhibited similar behavior, reducing IL-8 production, suggesting that both phenolic compounds and essential oils could contribute to IL-8 inhibition. YSF showed the highest antibacterial activity against H. pylori (6.3-7.1 log CFU reduction, depending on the strain) and lower MIC (0.08 mg/mL). Results obtained have shown that YE and SAF fractions (YPF and YSF) were effective as antioxidant, anti-inflammatory, and antibacterial agents regardless of the H. pylori strain characteristics.